KECENDERUNGAN PROFIL KEPRIBADIAN : INDIVIDU PHYSICALLY BROKEN HOME DAN BUNUH DIRI DITINJAU MELALUI 15 NEED EPPS (EDWARD PERSONAL PREFERENCE SCHEDULE) - Alfinyogia Rahman; Afi Rizqi Zakaria; Arya Firdhana Fakih (Flourishing Journal, 2022)
Abstract Lucky individuals get a family as the first and main social group that helps a person grow and develop. A person's personality will be formed as the interaction in the family goes, following the flow and patterns of education in it. The incompleteness of the family structure due to separation or the death of parents is what causes the family to be physically damaged, resulting in the family not being optimal and affecting personality development. Suicide is usually one of the most frequently used solutions, which often occurs in children who have just experienced a physically broken home. Individuals commit suicide when they feel depressed and think that they do not pay attention and benefit themselves in life. Symptoms will appear when the individual is about to commit suicide, either stellar or express. This research and article aims to determine the profile of children who have a family background. The purpose of this study itself is to determine the personality profile of someone with a physical broken home background based on the Edward Personal Preference Schedule (EPPS). The study used a descriptive method with a quantitative approach. The results of the study if physically broken home students have a high personality tendency on the Succorance and Aggression variables and low on the Intraception variable, Students from broken home families due to divorce have a high personality tendency on the Exhibition, Succorance, Heterosexuality and Aggression variables and low on the Achievement variable, Personality of early adulthood individuals with suicidal tendencies, namely the three subjects had high needs on the loyalty variable, affiliation variable, exhibition variable, success variable, and deficiency variable, and low needs on the dominance variable, resilience variable and heterosexual variable. Keywords: physically broken home, EPPS, suicide, personality. Abstrak Individu yang beruntung mendapatkan keluarga sebagai kelompok social pertama dan utama yang membantu tumbuhkembang dari kepribadian seseorang. Kepribadian seseorang akan terbentuk menjadi semakin baku seiring berjalannya interaksi di dalam keluarganya, mengikuti arus keharmonisan dan pola didik di dalamnya. Ketidaklengkapan susunan keluarga karena perpisahan ataupun kematian orang tua itulah yang dinamakan physically broken home mengakibatkan fungsi keluarga menjadi tidak optimal dan mempengaruhi perkembangan kepribadian. Bunuh diri biasanya menjadi salah satu solusi yang paling sering dipakai, yang sering terlintas pada anak yang baru mengalami physically broken home. Bunuh diri dilakukan individu ketika merasa depresi dan berfikir tidak adanya perhatian serta kebermanfaatan dirinya di dalam hidup. Gejala-gejala akan muncul ketika individu hendak melakukan tindakan bunuh diri baik tersirat maupun tersurat. Penelitian dan peninjauan artikel ini ditujukan guna mengetahui profil kepribadian Anak yang mempunyai latar belakang keluarga. Tujuan dari penelitian ini sendiri adalah untuk mengetahui profil kepribadian seseorang yang berlatar belakang physically broken home berdasarkan Edward Personal Preference Schedule (EPPS). Penelitian menggunakan metode deskriptif dengan pendekatan kuantitatif. Hasil penelitian didapati jika (1) Siswa physically broken home memiliki kecenderungan kepribadian tinggi pada variabel Succorance dan Aggression serta rendah pada variabel Intraception. (2) Siswa dari keluarga broken home karena perceraian kecenderungan kepribadiannya tinggi pada variabel Exhibition, Succorance, Heterosexuality dan Aggression serta rendah pada variabel Achievement. (3) Kepribadian individu usia dewasa awal dengan kecenderungan bunuh diri, yaitu ketiga subyek memiliki needs yang tinggi pada variabel deference, variabel affiliation, variabel exhibition, variabel succorance, dan variabel abasement, dan needs yang rendah pada variabel dominance, variabel endurance dan variabel heterosexual Kata kunci: physically broken home, EPPS, Bunuh diri, kepribadian